The Role of Anterior Cervical Discectomy and Fusion on Relieving Axial Neck Pain in Patients With Single-Level Disease: A Systematic Review and Meta-Analysis. Issue 3 (May 2020) - Oitment, Colby; Watson, Tracy; Lam, Victor; Aref, Mohammed; Koziarz, Alex; Kachur, Edward; Badhiwala, Jetan H.; Almenawer, Saleh A.; Cenic, Aleksa
Study Design: Systematic review and meta-analysis. Objectives: This study aims to evaluate the effects of anterior cervical decompression and fusion (ACDF) on axial neck pain in adult patients receiving surgery for myelopathy, radiculopathy, or a combination of both. Methods: Two independent reviewers completed a librarian-assisted search of 4 databases. Visual Analogue Scale (VAS) and Neck Disability Index (NDI) scores were extracted preoperatively and at 3, 6, 12, 24, 36, 48, and 48+ months postoperatively for ACDF groups and pooled using a random-effects model. Results: Of 17 850 eligible studies, 37 were included for analysis, totaling 2138 patients analyzed with VAS and 2477 with NDI score. Individual VAS mean differences were reduced at 6 weeks (−2.5 [95% confidence interval (CI): −3.5 to −1.6]), 3 months (−2.9 [−3.7 to −2.2]), 6 months (−3.2 [−3.9 to −2.6]), 12 months (−3.7 [−4.3 to −3.1]), 24 months (−4.0 [−4.4 to −3.5]), 48 months (−4.6 [−5.5 to −3.8]), and >48 months (−4.7 [−5.8 to −3.6]) follow-up ( P < .0001 for all endpoints). Individual NDI mean differences were reduced at 6 weeks (−26.7 [−30.9 to −22.6]), 3 months (−29.8 [−32.7 to −26.8]), 6 months (−31.2 [−35.5 to −26.8)], 12 months (−29.3 [−33.2 to −25.4]), 24 months (−28.9 [−32.6 to −25.2]), 48 months (−33.1 [−37.4 to −28.7]), and >48 months (−37.6 [−45.9 to −29.3]) follow-up ( P < .0001 for all endpoints). Conclusions: ACDF is associated with a significant reduction in axial neck pain compared with preoperative values in patients being treated specifically for myelopathy or radiculopathy. This influences the preoperative discussions surgeons may have with patients regarding their expectations for surgery. The effects seen are stable over time and represent a clinically significant reduction in axial neck pain.